Impacts of Coping Strategies for Electricity Load Shedding among University Students - Anwar Ali Malik, Parveen Akhter Memon, Hasnain Ali, Manthar Ali Mallah, Khuda Bux, Mansoor Ul Haq (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Electricity crisis is growing day by day which affects our routine life. The purpose of the study was to assess the impacts and coping strategies of electricity load shedding that wereadopted by university students. Methodology: The descriptive cross-sectional study was carried out among 384 university students during campus timings at the University of Sindh Jamshoro. The level of the confidence interval was set 95% with 0.05% of margin error. A convenient sampling technique was used. The raw data were analyzed and edited in MS Excel and then entered in SPSS version 16. Frequency and percentage were calculated for measuring the impact of load shedding and chi-square test was used where it needed. A p-value of less than 0.05 was considered statistically significant. Results: The mean age of the respondents was 21.7 years, ± 2.65. The findings of the present study showed 78% of students felt physically, mentally and emotionally ill due to load shedding. Our study revealed 71.61% of students who felt anxiety due to load shedding. A study result showed 41% of the respondents who became angry and caused physical violence. Present study also identified 77% of the participant’s sleep was disturbed. A study indicated 76.56% of student’s punctuality was affected. Our study inquired 75% students’ grades were affected and 87% students could not maintain concentration during lectures. Walking, physical exercise, and listening to music were identified as coping strategies. Conclusion: Electricity load shedding badly affects the overall performance of students including their punctuality, concentration during classes, and preparation of assignments, examinations, and results. Furthermore, the findings of this research should be confirmed in a cohort or longitudinal studies.